Electrospun Scaffolds for the Hypothermic Preservation of Cells - Barker, Sven-Alexander; Leal Marin, Sara; Roger, Yvonne; Hoffmann, Andrea; Zussman, Eyal; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):294